Marketing Strategy to Increase Brand Awareness (Case Study: Vego) - Handayani Wijaya; Harimukti Wandebori (Syntax Literate, 2025)
The rising popularity of vegetarianism and plant-based diets in Indonesia gives a unique opportunity for VEGO to enter a growing market. However, the brand meets obstacles such as low brand awareness and uneven sales, which limit its market reach and growth potential. The research being conducted analyzes techniques for increasing VEGO's brand awareness and competitiveness in the vegetarian food industry. The research adopts a mixed-methods approach, combining quantitative survey data from 206 respondents with qualitative insights from in-depth interviews. Cluster research revealed five customer groups with unique preferences, leading VEGO to choose Cluster 3: Sustainability Advocates as their major target market. Respondents in this cluster prioritize eco-friendly packaging, natural ingredients, and cost, which aligns with VEGO's basic principles and product offerings. The study uses marketing methods such as the STP framework, PESTEL analysis, and Porter's Five Forces model to examine market dynamics and create a customized marketing strategy. Key findings highlight the necessity of using digital platforms such as Instagram and TikTok for promotions, engaging with eco-conscious influencers, and implementing modern technology to improve product quality and shelf life. The proposed marketing strategy aims to strengthen VEGO's unique positioning as a sustainable, health-conscious, mushroom-based product brand. By addressing consumer requirements and aligning its strategy with developing market trends, VEGO expects to increase brand awareness, encourage customer loyalty, and achieve long-term success in the competitive vegetarian food market.